Is it possible to prevent female brain aging and Alzheimer’s disease? - Krzyczkowska-Sendrakowska, Magdalena (Menopause Review/Przegląd Menopauzalny, 2013)
All brain’s structures and functions are estrogen sensitive. Estrogens do influence neurotransmitters and neurons. They are also neuroprotective. Estrogens regulate the brain’s bio-energetic system by regulating glucose metabolism, and the process of oxidative phosphorylation. They influence the transporter’s substrates. Shortage of estrogens, by lowering glucose metabolism, leads to the brain’s hypometabolic state. Estrogens support the process of brain drawing energy from glucose, which prevents brain from drawing energy from other sources such as lipids. Such metabolic status favors the development of Alzheimer’s disease. Estrogens limit synthesis of the amyloid and protein tau and enhance activity of the dopamine, what reduces the risk of Alzheimer’s disease. There is a critical time when the hormonal therapy should be started in order to reduce the risk of Alzheimer’s disease. Starting the therapy within 5 years after menopause reduces the risk of Alzheimer’s disease by 30%. The risk will be limited if the hormonal therapy is used for ten years or longer.